PENERAPAN SISTEM VALUE STREAM MAPPING UNTUK PENINGKATAN HASIL PRODUKSI SPAREPART SEPEDA MOTOR MAINSTAND 2SD - Maulana Fajrian (Operations Excellence: Journal of Applied Industrial Engineering, 2018)
Consumers of two-wheeled vehicles in Indonesia continue to increase every year. This encourages manufacturers of two-wheeled vehicles to meet consumer needs by making vehicles in a timely manner. The biggest problem in two-wheel manufacturing companies is mainly the amount of delivery delay with a percentage of 67 percent originating from the line welding robot so that shipments to customers are not met. The purpose of this study is to improve production by applying the value stream mapping system. In the initial stage, cycle time, transportation time and lead time are analyzed. Next is the identification of waste that occurs on the Mainstand 2SD line for improvement using relayout.  After improvement, relayout lead time fell from 12 days to 6 days or down 50 percent. After improvement, production results have not reached the target with an average of 22.18 parts per hour while the target of 24 parts per hour is equivalent to the average yield of 7220.60 parts per month while the target is 8184 parts per month which means achieving the target of 94 percent.